UNJUK KERJA COOL BOX BERBASIS THERMOELEKTRIK COOLER DENGAN SINGLE DAN MULTI-STAGE TERMOELEKTRIK - Munawir Munawir; Mega Nur Sasongko; Nurkholis Hamidi (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2019)
Thermoelectric technology works by converting thermal energy into electricity directly or preferably. Thermoelectric technology works by converting thermal energy into electricity directly or preferably. Theuse of thermoelectric as a cooler in cool box systems has been extensively studied. The thermoelectric cool ability can be achieved depending on the design of a good system. Therefore, this study aims to determine the performance of thermoelectric cooler cool box based on single and multi stage. Tests carried out using cool boxes of dimensions of 31 cm x 19 cm x 24 cm witha thickness of 3 cm and with the TEC1 12706 module. The voltage used in each configuration is 12 Volts. Temperature data readings on laptops using DAQNavi_SDK data logger connected to type K thermocouples. The result showed the multi stage configuration reached a room temperature of around 19.3 oC and 21.8 oC for single stage. Meanwhile, the multi stage configuration COP value is 1.36 and with a single stage configuration is0.88. It can be concluded that the thermoelectric configuration has an influence on the performance of the cool box system. Keywords: Cool box, Thermoelectric module, Multi stage, single stage, COP